Achievement of Early Compressive Strength in Concrete Using Sporosarcina pasteurii Bacteria as an Admixture - Rakesh Chidara; Rahul Nagulagama; Smitha Yadav (Advances in Civil Engineering)
Often it is observed, attainment of early compressive strength in concrete is a challenge. Researchers have tried various admixtures to achieve the objective. This work addresses the issue of achieving early compressive strength in concrete using a bacterium called Sporosarcina pasteurii. The bacterium is characterised with the ability to precipitate calcium carbonate in the presence of any carbonate source and is known for its resistive capacity in extreme temperature and pressure zones. To establish the objective of gain in early strength around 192 concrete cubes were tested at 3, 7, 14, and 28 days and the results compared with controlled concrete. The bacterium was used in combination of chemicals and the dosage proportions were altered to achieve the desired M20 compressive strength at 28 days.